The Role of the Buccal Fat Pad in Facial Aesthetic Surgery. Issue 2 (August 2021) - Rohrich, Rod J.; Stuzin, James M.; Savetsky, Ira L.; Avashia, Yash J.; Agrawal, Nikhil A.; Prada, Margarita
Abstract : Summary: Social media have triggered a buccal fat pad excision frenzy. Not surprisingly, there is tremendous appeal of having a slimmer lower face and more defined jawline after undergoing a small intraoral procedure under local anesthesia. Although this procedure is great for social media and seemingly beneficial for jawline aesthetics, the evidence remains limited as to whether or not this is an effective long-term solution. How much the buccal fat pad persists or diminishes as we age is an area of debate. However, the possibility of causing premature aging and midface distortion in the long run is disconcerting.